Adrenergic CaV1.2 Activation via Rad Phosphorylation Converges at α1C I-II Loop. Issue 1 (22nd October 2020) - Papa, Arianne; Kushner, Jared; Hennessey, Jessica A.; Katchman, Alexander N.; Zakharov, Sergey I.; Chen, Bi-xing; Yang, Lin; Lu, Ree; Leong, Stephen; Diaz, Johanna; Liu, Guoxia; Roybal, Daniel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Changing activity of cardiac CaV 1.2 channels under basal conditions, during sympathetic activation, and in heart failure is a major determinant of cardiac physiology and pathophysiology. Although cardiac CaV 1.2 channels are prominently upregulated via activation of PKA (protein kinase A), essential molecular details remained stubbornly enigmatic. Objective: The primary goal of this study was to determine how various factors converging at the CaV 1.2 I-II loop interact to regulate channel activity under basal conditions, during β-adrenergic stimulation, and in heart failure. Methods and Results: We generated transgenic mice with expression of CaV 1.2 α1C subunits with (1) mutations ablating interaction between α1C and β-subunits, (2) flexibility-inducing polyglycine substitutions in the I-II loop (GGG-α1C ), or (3) introduction of the alternatively spliced 25-amino acid exon 9* mimicking a splice variant of α1C upregulated in the hypertrophied heart. Introducing 3 glycine residues that disrupt a rigid IS6–α-interaction domain helix markedly reduced basal open probability despite intact binding of CaV β to α1C I-II loop and eliminated β-adrenergic agonist stimulation of CaV 1.2 current. In contrast, introduction of the exon 9* splice variant in the α1C I-II loop, which is increased in ventricles of patients with end-stage heart failure, increased basal open probability but did not attenuate stimulatory response to β-adrenergic agonists when reconstituted heterologously with β2B and Rad or transgenically expressed in cardiomyocytes. Conclusions: Ca 2+ channel activity is dynamically modulated under basal conditions, during β-adrenergic stimulation, and in heart failure by mechanisms converging at the α1C I-II loop. CaV β binding to α1C stabilizes an increased channel open probability gating mode by a mechanism that requires an intact rigid linker between the β-subunit binding site in the I-II loop and the channel pore. Release of Rad-mediated inhibition of Ca 2+ channel activity by β-adrenergic agonists/PKA also requires this rigid linker and β-binding to α1C .